Welcome to beach town : a novel [large type] - Wiggs, Susan (Harper Large Print, an imprint of HarperCollins Publisher, 2023)
An idyllic California beach town is forced to reckon with a scandal when, at fancy Thornton Academy on California's coast, Nikki Graziola-a surfer's daughter there on scholarship-upends everyone by revealing a shocking secret in her valedictorian's speech.